2018
DOI: 10.1038/s41556-018-0145-9
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic niche functions and therapeutic opportunities

Abstract: Metastasis is an inefficient process, especially during colonization at a distant organ. This bottleneck underlies the importance of the metastatic niche for seeding and outgrowth of metastases. Here, we classify the common functions of different metastatic niches: anchorage, survival support, protection from external insults, licensing proliferation and outgrowth. We highlight the emerging role of the metastatic niche in maintaining cancer stemness and promoting immune evasion, and discuss therapeutic opportu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
98
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(99 citation statements)
references
References 149 publications
1
98
0
Order By: Relevance
“…Metastatic niches create a permissive environment for metastasis formation. The main consequence of the interaction between metastasis‐initiating cells and the premetastatic niche is enhanced cancer stemness and plasticity, as well as metastasis‐favouring immune interplay and editing . TDEs contain various components, including microRNAs, and can regulate intercellular communication in premetastatic sites .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metastatic niches create a permissive environment for metastasis formation. The main consequence of the interaction between metastasis‐initiating cells and the premetastatic niche is enhanced cancer stemness and plasticity, as well as metastasis‐favouring immune interplay and editing . TDEs contain various components, including microRNAs, and can regulate intercellular communication in premetastatic sites .…”
Section: Introductionmentioning
confidence: 99%
“…The main consequence of the interaction between metastasis-initiating cells and the premetastatic niche is enhanced cancer stemness and plasticity, as well as metastasis-favouring immune interplay and editing. 8 TDEs contain various components, including microRNAs, and can regulate intercellular communication in premetastatic sites. [9][10][11] MicroRNAs can be delivered into cells within microvesicles, apoptotic bodies, lipoproteins and ribonucleoproteins.…”
mentioning
confidence: 99%
“…Vascular leakage and infiltration of myeloid cells were important for the response to doxorubicin or cisplatin in breast carcinomas . These findings have underscored the importance of considering the role of the tumor microenvironment when designing chemotherapeutic strategies …”
Section: Translational Potential Of Iv‐mpm For Cancermentioning
confidence: 99%
“…33 These findings have underscored the importance of considering the role of the tumor microenvironment when designing chemotherapeutic strategies. 148 IV-MPM can be used to monitor therapy response and improve already effective therapies, such as immunotherapy. Adoptive cell therapy and cyclophosphamide (ACT-CTX) is one of the most effective treatments against melanoma.…”
Section: IVmentioning
confidence: 99%
“…Prior to the formation of overt metastatic disease, DTCs persist in the brain for months or years, and effective engagement with the metastatic niche is essential for colonization and outgrowth (Harper et al, 2016; Hosseini et al, 2016; Massagué and Obenauf, 2016; Sosa et al, 2014 . While the classic 'seed and soil' hypothesis highlights the importance of optimal DTCs arriving in a permissive metastatic microenvironment, recent studies into metastatic seeding, dormany, and outgrowth have revealed dynamic coevolutionary processes between DTCs and the metastatic niche (CeliàTerrassa and Kang, 2018) . Indeed, successful metastatic adaptation requires organspecific interactions with the surrounding parenchymal cells and extracellular matrix (Obenauf and Massagué, 2015) , and the diversity of these interactions (Chen et al, 2016; ContrerasZárate et al, 2019; Er et al, 2018; Schnepp et al, 2017; Zhang et al, 2015 , combined with the evolving heterogeneity of the DTCs themselves, renders the mechanistic dissection required for the development of treatment options challenging.…”
Section: Introductionmentioning
confidence: 99%